Advances and current trends in biomechanics : proceedings of the 9th Portuguese Congress on Biomechanics, CNB2021, 19 - 20 February 2021, Porto, Portugal /: proceedings of the 9th Portuguese Congress on Biomechanics, CNB2021, 19 - 20 February 2021, Porto, Portugal. (2021) - Unknown
No abstract available